SISTEM PAKAR DIAGNOSA PENYAKIT PADA IBU HAMIL DENGAN METODE FORWARD CHAINING DAN NAIVE BAYES (INTI TALAFA, 2024)
Disease in pregnant women is a disease suffered during pregnancy, lack of knowledge about the symptoms that are felt during pregnancy makes pregnant women ignore certain symptoms that can indicate dangerous diseases and become an indirect cause of death for the mother and baby in the womb. In addition, the risk of maternal death is also higher due to delays in making a decision to be referred. Based on this, an expert system was created where this system acts as an expert in diagnosing diseases in pregnant women. This system has 22 symptoms including nausea, vomiting, dizziness and so on and there are 5 diseases namely anemia, hemorrhoids, preeclampsia, placenta previa and Gestational Diabetes. By using the methodForward Chaining and Naïve Bayes which can help identify diseases during pregnancy based on the symptoms experienced by pregnant women. This application is web-based so that patients can access the application directly even though they are not at the Puskesmas. Based on testing by entering symptoms, namely blood pressure over 140/90 mm/Hg, easy thirst, blurred vision, pain in the pit of the stomach, and nausea, the results of system diagnosis and manual calculations have the same results, namely Preeclampsia 6.61%, Diabetes Gestional 66 .73% and Anemia 26.65%.